Genome-wide identification and expression analysis of the KCS gene family in soybean (Glycine max) reveal their potential roles in response to abiotic stress - Gong, Yujie; Wang, Deying; Xie, Haojie; Zhao, Zewei; Chen, Yuyue; Zhang, Dongxue; Jiao, Yexuan; Shi, Mengmeng; Lv, Peng; Sha, Qi; Yang, Jing; Chu, Pengfei; et al. (Frontiers in Plant Science, 2023)
Very long chain fatty acids (VLCFAs) are fatty acids with chain lengths of 20 or more carbon atoms, which are the building blocks of various lipids that regulate developmental processes and plant stress responses. 3-ketoacyl-CoA synthase encoded by the KCS gene is the key rate-limiting enzyme in VLCFA biosynthesis, but the KCS gene family in soybean (Glycine max) has not been adequately studied thus far. In this study, 31 KCS genes (namely GmKCS1 -GmKCS31) were identified in the soybean genome, which are unevenly distributed on 14 chromosomes. These GmKCS genes could be phylogenetically classified into seven groups. A total of 27 paralogous GmKCS gene pairs were identified with their Ka/Ks ratios indicating that they had undergone purifying selection during soybean genome expansion. Cis-acting element analysis revealed that GmKCS promoters contained multiple hormone-and stress-responsive elements, indicating that GmKCS gene expression levels may be regulated by various developmental and environmental stimuli. Expression profiles derived from RNA-seq data and qRT-PCR experiments indicated that GmKCS genes were diversely expressed in different organs/tissues, and many GmKCS genes were found to be differentially expressed in the leaves under cold, heat, salt, and drought stresses, suggesting their critical role in soybean resistance to abiotic stress. These results provide fundamental information about the soybean KCS genes and will aid in their further functional elucidation and exploitation.